Dial A for Aunties - Sutanto, Jesse Q. (Berkley, 2021)
"What happens when you mix 1 (accidental) murder with 2 thousand wedding guests, and then, toss in a possible curse on 3 generations of an immigrant Chinese-Indonesian family? You get 4 meddling Asian aunties coming to the rescue! When Meddelin Chan ends up accidentally killing her blind date, her meddlesome mother calls for her even more meddlesome aunties to help get rid of the body. Unfortunately, a dead body proves to be a lot more challenging to dispose of than one might anticipate-especially when it is accidentally shipped in a cake cooler to the over-the-top billionaire wedding that Meddy, her Ma, and her aunties are working, at an island resort on the California coastline. It is the biggest job yet for their family wedding business-"Don't leave your big day to chance, leave it to the Chans!"-and nothing, not even an unsavory corpse, will get in the way of her aunties' perfect buttercream-cake flowers. But things go from inconvenient to downright torturous when Meddy's great college love-and biggest heartbreak-makes a surprise appearance amid the wedding chaos. Is it possible to escape murder charges, charm her ex back into her life, and pull off a stunning wedding, all in one weekend?"--